Analisis Pendapatan Usaha Peternakan Ayam Ras Petelur Di CV Balita Madani Desa Soulove Kecamatan Dolo Kabupaten Sigi - Nursamsi, Nursamsi; Windari, Iin Ika Sri (MACROCEPHALON : Jurnal Ilmu Peternakan, 2025)
This study aims to analyze the income of layer chicken farming by calculating production costs, revenue, and net profit. The research employed a descriptive quantitative method with a case study approach on a layer poultry farming unit. Data were collected through interviews, observations, and documentation, and analyzed by calculating variable costs, fixed costs, total costs, revenue, and income. The results showed that the total variable cost reached IDR 2,398,000,000, while the fixed cost was IDR 230,353,000, resulting in a total production cost of IDR 2,628,353,000. Revenue was obtained from the sales of 96,725 racks of eggs and 1,800 culled hens, with a total value of IDR 4,424,625,000. The net income generated amounted to IDR 1,796,272,000, indicating that layer chicken farming is economically feasible and has promising business prospects. These findings emphasize that efficient management of production costs, particularly feed costs, plays a crucial role in improving the profitability of layer poultry farming.